2008
DOI: 10.1029/2008ja013158
|View full text |Cite
|
Sign up to set email alerts
|

On blanketing sporadic E and polarization effects near the equatorial electrojet

Abstract: [1] A number of puzzling features have been observed that occur during the day in the vicinity of the equatorial electrojet (EEJ). They include (1) an equatorial belt, essentially collocated with the EEJ, that is virtually devoid of blanketing sporadic E (E sb ); (2) appearances of E sb within that ''forbidden'' belt but only when the EEJ is weak or reversed (i.e., a counterelectrojet); (3) occasional appearances of a secondary current layer above the EEJ; and (4) observations at 4.3°N dip latitude of a latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 76 publications
5
47
0
Order By: Relevance
“…In view of the theories summarized above, we understand that the E sb observed at the equatorial region is either formed locally (Reddy and Devasia, 1973) or transported from the off-equatorial region (Chandra and Rastogi, 1975;Tsunoda, 2008). However, the contribution from each of the abovementioned processes to E sb occurrence observed in the different seasons is not known.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In view of the theories summarized above, we understand that the E sb observed at the equatorial region is either formed locally (Reddy and Devasia, 1973) or transported from the off-equatorial region (Chandra and Rastogi, 1975;Tsunoda, 2008). However, the contribution from each of the abovementioned processes to E sb occurrence observed in the different seasons is not known.…”
Section: Discussionmentioning
confidence: 95%
“…For the formation of E sb at the equator, the authors have also suggested the transport mechanism of ionized E sb layer from off-equatorial latitudes to equatorial latitudes in the presence of horizontal wind with a significant north-south component. However, they could not establish the link between weak EEJ and E sb occurrence, which is addressed by Tsunoda (2008) for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations